1269 Five Year Propensity Matched Outcomes of Minimally Invasive vs Conventional Isolated Aortic Valve Surgery. (12th October 2021) - Oo, S; Khan, A; Chan, J; Vohra, H
Abstract: Aim: To analyse the early and mid-term outcomes of the patients undergoing conventional isolated aortic valve replacement (CAVR) versus minimally invasive isolated aortic valve replacement (MIAVR). Method: This is a single centre retrospective study involving 653 patients who underwent isolated aortic valve replacement either via CAVR (n = 516) or MIAVR (n = 137) between August 2015 and March 2020. Using pre-operative characteristics, patients were propensity matched (PM) to produce 114 matched pairs. Assessment of peri-operative outcomes, early and mid-term survival and echocardiographic parameters was performed. Results: PM analysis showed the larger sized aortic valve prosthesis were inserted in the MIAVR group (22.8±2.5mm) compared to CAVR group (22.0±2.2mm)(p = 0.010). CPB time was longer with MIAVR (94.4±19.5mins) compared to CAVR (83.1 + 33.3; p = 0.003). There were no differences in the early post-operative complications and mortality between the two groups. Follow-up echocardiographic data showed significant difference in mean aortic valve gradients between CAVR and MIAVR groups (17.3±8.2mmHg and13.0±5.1mmHg, respectively; p = 0.001). There was no significant difference between CAVR and MIAVR in the mid-term survival at 3 years. (log-rank test p = 0.314). Conclusions: This study found that larger aortic valve sizes with lower mean gradients are being implanted in the MIAVR group. Despite the longer CPB time in the MIAVR group, there was no significant difference in the early complications, mortality, and mid-term survival between MIAVR and CAVR. Further studies will be required to analyse the long-term survival.